HUBUNGAN TINGKAT PENGETAHUAN DAN KEPATUHAN DENGAN KEBERHASILAN PENGOBATAN PASIEN TUBERKULOSIS DI PUSKESMAS TELAGA MURNI, CIKARANG - Salamah, Hanifah Ikka; Dewi, Masita Sari; Adiwisastra, Nuzul Gyanata; Marselina, Marselina (Jurnal Buana Farma, 2025)
Tuberculosis (TB) remains a public health problem in Indonesia, with treatment success rates that have not yet reached national targets, partly influenced by patient behavioral factors. Patient knowledge and medication adherence are considered important determinants of TB treatment outcomes. This study aimed to analyze the relationship between patients’ knowledge level and medication adherence with tuberculosis treatment success at Telaga Murni Community Health Center, West Cikarang District. This quantitative study employed a correlational analytical design using a cross-sectional approach. The study sample consisted of 80 adult pulmonary TB patients selected through total sampling. Data were collected through structured interviews using a knowledge questionnaire and the Morisky Medication Adherence Scale-8 (MMAS-8), as well as medical record reviews to assess treatment success. Data were analyzed using univariate and bivariate analysis with the Chi-square test. The majority of respondents were female (58.7%), aged 17–25 years (35%), had senior high school education (50%), and were unemployed (51.2%). Most respondents received treatment observer (PMO) assistance (58.8%), were in the advanced treatment phase (58.7%), and were classified under treatment category I (97.5%). Good knowledge levels were identified in 90% of respondents, while low medication adherence was observed in 85%. Treatment success was achieved in 12.5% of respondents. Chi-square analysis showed no statistically significant relationship between knowledge level and treatment success (p = 0.827), nor between medication adherence and treatment success (p = 0.365). In conclusion, patient knowledge level and medication adherence were not significantly associated with tuberculosis treatment success, suggesting the need for broader multidisciplinary intervention strategies.